The impacts of donor transitions on health systems in middle-income countries: a scoping review. Issue 9 (29th July 2022) - Huffstetler, Hanna E; Bandara, Shashika; Bharali, Ipchita; Kennedy Mcdade, Kaci; Mao, Wenhui; Guo, Felicia; Zhang, Jiaqi; Riviere, Judy; Becker, Liza; Mohamadi, Mina; Rice, Rebecca L; King, Zoe; et al.
Abstract: As countries graduate from low-income to middle-income status, many face losses in development assistance for health and must 'transition' to greater domestic funding of their health response. If improperly managed, donor transitions in middle-income countries (MICs) could present significant challenges to global health progress. No prior knowledge synthesis has comprehensively surveyed how donor transitions can affect health systems in MICs. We conducted a scoping review using a structured search strategy across five academic databases and 37 global health donor and think tank websites for literature published between January 1990 and October 2018. We used the World Health Organization health system 'building blocks' framework to thematically synthesize and structure the analysis. Following independent screening, 89 publications out of 11 236 were included for data extraction and synthesis. Most of this evidence examines transitions related to human immunodeficiency virus/Acquired Immune Deficiency Syndrome (AIDS; n = 45, 50%) and immunization programmes ( n = 14, 16%), with a focus on donors such as the Global Fund to Fight AIDS, Tuberculosis and Malaria ( n = 26, 29%) and Gavi, the Vaccine Alliance ( n = 15, 17%). Donor transitions are influenced by the actions of both donors and country governments, with impacts on every component of the health system. Successful transition experiences show that leadership, planning, and pre-transition investments in a country's financial, technical, and logistical capacity are vital to ensuring smooth transition. In the absence of such measures, shortages in financial resources, medical product and supply stock-outs, service disruptions, and shortages in human resources were common, with resulting implications not only for programme continuation, but also for population health. Donor transitions can affect different components of the health system in varying and interconnected ways. More rigorous evaluation of how donor transitions can affect health systems in MICs will create an improved understanding of the risks and opportunities posed by donor exits.